2016
DOI: 10.1038/srep20152
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Giant-Gap Quantum Spin Hall Insulator in Chemically Decorated Plumbene Monolayer

Abstract: Quantum spin Hall (QSH) effect of two-dimensional (2D) materials features edge states that are topologically protected from backscattering by time-reversal symmetry. However, the major obstacles to the application for QSH effect are the lack of suitable QSH insulators with a large bulk gap. Here, we predict a novel class of 2D QSH insulators in X-decorated plumbene monolayers (PbX; X = H, F, Cl, Br, I) with extraordinarily giant bulk gaps from 1.03 eV to a record value of 1.34 eV. The topological characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(96 citation statements)
references
References 41 publications
7
89
0
Order By: Relevance
“…Afterwards, several candidate materials are proposed to overcome the issue in graphene for the observation of QSH effect. These samples include silicene10, germanene11, stanene12, plumbene13, bismuth14, and arsenene15, in which they exhibit the topology properties alike to grapheme, but their nontrivial bulk gaps are still small. Motivated by the experimental synthesis of hydrogenated germanene (GeH)16, the chemical functionalization on honeycomb structure, e.g., Bi/Sb/As17181920 and Ge/Sn/Pb films21222324252627, has been proposed to host QSH effect with enhanced band gaps.…”
mentioning
confidence: 99%
“…Afterwards, several candidate materials are proposed to overcome the issue in graphene for the observation of QSH effect. These samples include silicene10, germanene11, stanene12, plumbene13, bismuth14, and arsenene15, in which they exhibit the topology properties alike to grapheme, but their nontrivial bulk gaps are still small. Motivated by the experimental synthesis of hydrogenated germanene (GeH)16, the chemical functionalization on honeycomb structure, e.g., Bi/Sb/As17181920 and Ge/Sn/Pb films21222324252627, has been proposed to host QSH effect with enhanced band gaps.…”
mentioning
confidence: 99%
“…The overlap between valence band maximum (VBM) and conduction band minimum (CBM) at the Γ point is decreased and finally a very small electronic indirect electronic gap is opened at the Γ point. To investigate the topological phase of FBSn we calculate the Z 2 topological invariant by crossing the parities of occupied bands [4,5,35,36]. Table 1 indicates the occupied bands paritiy at four TRIM points for FBSn unders 2 percent of biaxial tensile strain.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the relatively large atomic mass of tin atoms the intrinsic spin-orbit interaction opens an energy gap in the electronic structure of stanene which is around 70 meV [24,28]. Theoretical calculations predict a larger gap for halogenated monolayer [24] and ethynyle-derivative [4] stanene, as well as chemically decorated plumbene [5], that suggest these structures for application in nanodevices based on topological insulators. Indeed, it was shown that oxygen adsorption may cause topological behavior to trivial phase transition in stanene nanoribbons [25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations